CHITOSAN COLLAGEN HYDROGEL: A POTENTIAL SCAFFOLD BIOMATERIAL FOR PERIODONTAL REGENERATIVE TREATMENT - Dharmmesti Anindita Wijayanti; Dahlia Herawati; Vincensia Maria Karina; Kwartarini Murdiastuti (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Hydrogels are considered a promising scaffold biomaterial for regenerative periodontal treatment. The development of collagen and chitosan based hydrogels can improve the final characteristics of the hydrogel. Review: Collagen and chitosan are the two main materials used to design scaffolds for tissue engineering. Collagen is a material that is often used to develop hydrogels because it has the advantage of high biocompatibility. In the biomedical field, collagen is often used as a drug delivery system. Collagen has weak mechanical strength so other biomaterials are needed for its use. Chitosan material has high biocompatibility and a slow degradation rate. So the combination of these two materials is a strategic choice for making promising biomaterial scaffolds in periodontal regenerative treatment. Conclusion: Chitosan collagen hydrogel is a potential scaffold biomaterial for periodontal regenerative treatment.